Indicators to assess the functionality of clubfoot clinics in low-resource settings: a Delphi consensus approach and pilot study. Issue 5 (19th May 2018) - Smythe, Tracey; Mudariki, Debra; Foster, Allen; Lavy, Christopher
Abstract: Background: This study aims to determine the indicators for assessing the functionality of clubfoot clinics in a low-resource setting. Methods: The Delphi method was employed with experienced clubfoot practitioners in Africa to rate the importance of indicators of a good clubfoot clinic. The consistency among the participants was determined with the intraclass correlation coefficient. Indicators that achieved strong agreement (mean≥9 [SD <1.5]) were included in the final consensus definition. Based on the final consensus definition, a set of questions was developed to form the Functionality Assessment Clubfoot Clinic Tool (FACT). The FACT was used between February and July 2017 to assess the functionality of clinics in the Zimbabwe clubfoot programme. Results: A set of 10 indicators that includes components of five of the six building blocks of a health system—leadership, human resources, essential medical equipment, health information systems and service delivery—was produced. The most common needs identified in Zimbabwe clubfoot clinics were a standard treatment protocol, a process for surgical referrals and a process to monitor dropout of patients. Conclusions: Practitioners had good consistency in rating indicators. The consensus definition includes components of the World Health Organization building blocks of health systems. Useful information was obtained on how to improve the services in the Zimbabwe clubfoot programme.